The association between intelligence and financial literacy: A conceptual and meta-analytic review - Callis, Zoe; Gerrans, Paul; Walker, Dana L.; Gignac, Gilles E. (My University, 2023)
Financial literacy is positively associated with intelligence, with typically moderate to large effect sizes across studies. The magnitude of the effect, however, has not yet been estimated meta-analytically. Such results suggest financial literacy may be conceptualised as a possible cognitive ability within the Cattel-Horn-Carroll (CHC) model of cognitive abilities. Consequently, we present a psychometric meta-analysis that estimated the true score correlation between cognitive ability and financial literacy. We identified a large, positive correlation with general intelligence (r’ = .62; k = 64, N = 62,194). We also found that financial literacy shared a substantial amount of variance with quantitative knowledge (Gq; via numeracy; r’ = .69; k = 42, N = 35,611), comprehension knowledge (crystallised intelligence; Gc; r’ = .48; k = 14, N = 10,835), and fluid reasoning (fluid intelligence; Gf; r’ = .48; k =20, N = 15,101). Furthermore, meta-analytic structural equation modelling revealed Gq partially mediated the association between cognitive ability (excluding Gq) and financial literacy. Additionally, both Gc and Gq had significant direct effects on financial literacy, whereas the total effect of Gf on financial literacy was fully mediated by a combination of Gc and Gq. While the meta-analyses provide preliminary support for the potential inclusion of financial literacy as primarily a Gc or Gq ability within the CHC taxonomy (rather than Gf), the review revealed that very few studies employed comprehensive cognitive ability measures and/or psychometrically robust financial literacy tests. Consequently, the review highlighted the need for future factor analytic research to evaluate financial literacy as a candidate for inclusion in the CHC taxonomy.
Intelligence
Keywords: Income, wealth and finances